A novel electromagnet-triggered pillar valve and its application in immunoassay on a centrifugal platform. Issue 10 (25th April 2019) - Chen, Yiqi; Shen, Minjie; Zhu, Yunzeng; Xu, Youchun
Abstract : A novel electromagnet-triggered pillar valve is proposed and applied to realize automatic and multiplex immunoassay on a centrifugal platform. Abstract : The lab-on-a-disc is a powerful microfluidic platform that skillfully takes advantage of centrifugal force to controllably drive liquids with the assistance of passive or active valves. However, the passive valves are mainly triggered by the rotation speed and can be easily influenced by the surface chemistry of the channel, while the active valves usually require a complicated fabrication or actuation procedure. In this study, a novel active valve that can be easily triggered by an electromagnet was proposed and applied on the centrifugation platform. This valve, named the electromagnet-triggered pillar (ETP) valve, consisted of a metal pin and pressure sensitive adhesive (PSA) tape, and is closed until the pin is lifted up by an electromagnet to partially separate the PSA tape from the substrate. As a typical application, this valve is utilized to construct a centrifugal chip for mycotoxin detection. With four ETP valves in a unit, the sample and liquid reagents can be sequentially released into the reaction chamber that was spotted with mycotoxin conjugates to accomplish the whole immunoassay. Four mycotoxins (aflatoxin B1, ochratoxin A, T-2 toxin, and zearalenone) were simultaneously detected on this chip with limits of detection lower than the permissible limits set by the regulatory agencies of China, demonstrating the practicability of this easy-to-use active valve.